Pectin Chemistry and Cellulose Crystallinity Govern Pavement Cell Morphogenesis in a Multi-Step Mechanism. Issue 1 (30th July 2019) - Altartouri, Bara; Bidhendi, Amir J; Tani, Tomomi; Suzuki, Johnny; Conrad, Christina; Chebli, Youssef; Liu, Na; Karunakaran, Chithra; Scarcelli, Giuliano; Geitmann, Anja
Abstract : Demethylated pectin is involved in initiating morphogenetic events in pavement cells, and crystalline cellulose plays a role during feedback - mediated augmentation of waviness. Abstract: Simple plant cell morphologies, such as cylindrical shoot cells, are determined by the extensibility pattern of the primary cell wall, which is thought to be largely dominated by cellulose microfibrils, but the mechanism leading to more complex shapes, such as the interdigitated patterns in the epidermis of many eudicotyledon leaves, is much less well understood. Details about the manner in which cell wall polymers at the periclinal wall regulate the morphogenetic process in epidermal pavement cells and mechanistic information about the initial steps leading to the characteristic undulations in the cell borders are elusive. Here, we used genetics and recently developed cell mechanical and imaging methods to study the impact of the spatio-temporal dynamics of cellulose and homogalacturonan pectin distribution during lobe formation in the epidermal pavement cells of Arabidopsis ( Arabidopsis thaliana ) cotyledons. We show that nonuniform distribution of cellulose microfibrils and demethylated pectin coincides with spatial differences in cell wall stiffness but may intervene at different developmental stages. We also show that lobe period can be reduced when demethyl-esterification of pectins increases under conditions of reduced cellulose crystallinity. Our data suggest that lobe initiation involves a modulation of cell wall stiffness through local enrichment in demethylated pectin, whereas subsequent increase in lobe amplitude is mediated by the stress-induced deposition of aligned cellulose microfibrils. Our results reveal a key role of noncellulosic polymers in the biomechanical regulation of cell morphogenesis.